How to find a four-leaf clover : what autism can teach us about difference, connection, and belonging - Rodgers, Jodi (Little, Brown Spark, 2024)
A special-education teacher with thirty years of experience working with autistic people gives readers a deeper understanding of and appreciation for the neurodiverse community and looks at ways we can develop more meaningful connections with others.